2014 Guideline for the Management of Patients with Atrial Fibrillation (AFib) - Haque, Harisul (University Heart Journal, 2014)
DOI: http://dx.doi.org/10.3329/uhj.v9i1.19429 University Heart Journal Vol. 9, No. 1, January 2013; 1-2